Pressed roofing tile based on cementitious material and basalt powder: Technological and toxicological characterization - Jesus,Franciele B. T. de (2022)
Abstract This study aims to develop a pressed concrete roofing tile from powder technology containing basalt powder in substitution of fine sand (aggregate) for application in building covers. Specimens were submitted to technological and toxicological characterization. Hence, pressed specimens based on cement and basalt powder were analyzed. In the bending strength test, the pressed samples containing a cement:basalt mass ratio of 1:6, water content of 5% and specific pressure of 25 MPa revealed a value of 3.82 ±0.46 MPa at 28 days of curing, while the molded samples (reference) with cement:sand mass ratio of 1:5 and 15% water content revealed 1.72 ±0.86 MPa. This composition, containing cement and basalt powder, is not toxic, confirming the possibility for total replacement of sand by basalt powder. Thus, it was demonstrated that the technical viability for the proposed process and the use of basalt powder to obtain pressed flat concrete roof tile meets technical requirements and standards, compared to conventional concrete roofing tiles.